Infrared signal of the lobed mixer with external air mixing. (6th September 2021) - Choi, S.M.; Jang, H.S.; Park, H.H.
Abstract: In order to know the characteristics of reducing the exhaust gas infrared signal of the lobed mixer according to the external air mixing ratio, an infrared signal and temperature distribution measurement using a micro-turbojet engine is performed. A certain amount of compressed air is supplied through an external duct mounted on the micro-turbojet engine exhaust to simulate bypass flow, which is mixed with high-temperature core air and ejected to the atmosphere. The exhaust nozzle used in the experiment is a lobed mixer with a lobe of sinusoidal shape and is designed to have a penetration of 0.2. Exhaust gas temperature and infrared signal are measured according to distance from nozzle outlet under conditions of bypass ratio of 0.5, 1.0 and 1.4. Infrared reduction rates are compared to data without compressed air supply. As a result of the experiment, as the bypass ratio increased, the infrared signal of the exhaust gas and the temperature decrease with bypass ratio increase, and in the case of a bypass ratio of 1.4, the effect of reducing the temperature is observed even at a long distance. In addition, we compared the results of previous studies of a simple cone shape without mixer with infrared reduction effect. The results show that the lobed mixer has a greater effect on reducing the temperature of the exhaust gas and reducing the infrared signal than the cone nozzle. The structure of the mixed jet flow is also studied through Schlieren visualisation and 3D temperature distribution.